Human umbilical cord–derived mesenchymal stem cells improve chronic pancreatitis in rats via the AKT-mTOR-S6K1 signaling pathway. Issue 1 (1st January 2021) - Kong, Lijun; Xu, Xiangxiang; Zhang, Hewei; Zhou, Yi; Huang, Hongjian; Chen, Bicheng; Zhou, Zhenxu
ABSTRACT: Chronic pancreatitis (CP) is a progressive inflammatory disease. In clinical treatment, many patients cannot get a timely diagnosis and effective treatment due to the lack of early diagnosis indicators. Mesenchymal stem cells have immunomodulatory and anti-inflammatory effects, and have broad application prospects in treating auto-immune diseases and inflammatory diseases. This study aimed to clarify the mechanisms of human umbilical cord mesenchymal stem cells (HUCMSCs) in the treatment of CP. The rats were randomly divided into four groups, with six rats in each group: control group, CP group, CP + HUCMSCs–treated group I, and CP + HUCMSCs–treated group II. We evaluated the levels of inflammatory factors, fibrosis and apoptosis markers, detected the protein expression levels of AKT-mTOR-S6K1 and assessed histological changes of the pancreas. The results showed that HUCMSCs not only inhibited the secretion of inflammatory cytokines and activation of pancreatic stellate cells but also suppressed the apoptosis of acinar cells. Further investigation revealed that HUCMSCs noticeably suppressed the AKT-mTOR-S6K1 pathway in the pancreatic tissue of DBTC-induced CP. In addition, the therapeutic effect of HUCMSCs injected into the inferior vena cava and left gastric artery in the CP model was also observed, thus providing the basis for the clinical application of intervention measures. Abstract : uf0001